Telepoint: lessons in high technology product marketing - Bence, Valerie (Cranfield University, 1994)
In 1991 Telepoint joined the ranks of notorious marketing failures, like Betamax and the Sinclair C5. This paper will address the issues connected with this failure and the interaction with established thinking on high technology marketing, new product innovation and the risks associated with entering a nascent market sector.